Predicting Medical Students’ Current Attitudes Toward Psychiatry, Interest in Psychiatry, and Estimated Likelihood of Working in Psychiatry: A Cross-Sectional Study in Four European Countries - Warnke, Ingeborg; Gamma, Alex; Buadze, Maria; Schleifer, Roman; Canela, Carlos; Strebel, Bernd; Tényi, Tamás; Rössler, Wulf; Rüsch, Nicolas; Liebrenz, Michael (Frontiers in Psychiatry, 2018)
Psychiatry as a medical discipline is becoming increasingly important due to the high and increasing world-wide burden associated with mental disorders. Surprisingly, however, there is a lack of young academics choosing psychiatry as a career. Previous evidence on medical students’ perspectives is abundant but has methodological shortcomings. Therefore, by attempting to avoid previous shortcomings, we aimed to contribute to a better understanding of the predictors of the following three outcome variables: current medical students’ attitudes towards psychiatry, interest in psychiatry and estimated likelihood of working in psychiatry. The sample consisted of N = 1356 medical students at 45 medical schools in Germany and Austria as well as regions of Switzerland and Hungary with a German language curriculum. We used snowball sampling via Facebook with a link to an online questionnaire as recruitment procedure. Snowball sampling is based on referrals made among people. This questionnaire included a German version of the Attitudes Towards Psychiatry Scale (ATP-30-G) and further variables related to outcomes and potential predictors in terms of sociodemography (e.g. gender) or medical training (e.g. curriculum-related experience with psychiatry). Data were analysed by linear mixed models and further regression models. On average, students had a positive attitude to and high general interest in, but low professional preference for, psychiatry. A neutral attitude to psychiatry was partly related to the discipline itself, psychiatrists or psychiatric patients. Female gender and previous experience with psychiatry, particularly curriculum-related and personal experience, were important predictors of all outcomes. Students in the first years of medical training were more interested in pursuing psychiatry as a career. Furthermore, the country of the medical school was related to the outcomes. However, statistical models explained only a small proportion of variance. The findings indicate that particularly curriculum-related experience is important for determining attitudes towards psychiatry, interest in the subject and self-predicted professional career choice. We therefore encourage the provision of opportunities for clinical experience by psychiatrists. However, further predictor variables need to be considered in future studies.